Konstruksi Sosial Pedagang Pasar dalam Strategi Bertahan Hidup pada Masa Pandemi Covid-19 - Dear Lova Sukoco; Fahmi Hidayat; Wisnu Wardhana (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This paper aims to explain the existence of traditional markets as an example towards endemic. This research is an attempt to awaken people who are still doubtful about the existence of post-pandemic COVID-19, and this makes herd immunity, which is the main goal as well as a way to end the pandemic, and awareness of society is the key to make it happen. This study uses a qualitative paradigm with an ethnographic approach. Data collection was carried out using the method of observation, documentation and also interviews. The results of the study found that the condition of traditional markets during the pre-pandemic period was not much different from what experienced by the environment or public area, but it became different when the recovery process began where traditional markets managed to reach the stage of herd immunity earlier than other social environments. Hence, traditional markets has its own way to survive on pandemic. Existence of this research is aim to the endemic situation and economic recovery will be realized more quickly, especially for people who have managed to survive the pandemic so that endemic situations that happen faster can make people prepare for the possibility of worst situations in the future.